An International Review – Carrying the Torch of Anthony D. Smith’s Goal to Map the Field of Nationalism Studies - Eric Taylor Woods; Robert Schertzer (Studies on National Movements, 2022)
We are delighted to provide readers of Studies of National Movements (SNM) a brief update on the recent work and future directions of the State of Nationalism (SoN).